MENINGKATKAN KEMAMPUAN BERPIDATO PADA SISWA KELAS VI MELALUI TEKNIK MODELING DI SD KATOLIK NITA 1 SIKKA, NUSA TENGGARA TIMUR - KATHARINA NONA RUFIYATI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Low speech ability is a problem in learning Indonesian. To overcome this, appropriate techniques are needed, one of them is by applying modeling techniques. The objectives of this study are (i) to improve the process of applying modeling techniques in learning speech skills in grade VI students of Catholic Nita 1 Elementary School; (ii) to improve the speech learning outcomes by applying modeling techniques to grade VI students of the Catholic Nita 1 Elementary School. This study is a qualitative study. The research data was taken from teacher activities and student activities. Data collection techniques in this study were observation, interviews, and documentation. Data analysis was carried out by observing the activities of teachers and students in carrying out the learning process using modeling techniques. The resulting data is transcribed in tabular form. This research was conducted in two meetings, I &II. The results showed that (i) The process of applying modeling techniques in speech learning made students more enthusiastic and very enthusiastic. The improvement was seen from student activities and teacher activities in the learning process of giving speeches; (ii) The results of students’ speech abilities include linguistic abilities and non-linguistic abilities. The ability of language from the aspect of speech accuracy increased by 18.3. The intonation aspect increased by 24.0. The word choice aspect increased by 13.0. The non-linguistic ability from the aspect of reasonable attitudes increased by 18.3. The view aspect increased by 15.3. The facial aspect increased by 19.0. The loudness aspect increased by 19.0. The aspect of fluency increased by 20.0. At the first meeting, students who are 57% incomplete and 43% complete with an average value of 66.8 students’ speech ability with the category of quite capable. At the second meeting, students who had not completed 17% and who completed 83% with an average value of students’ speech ability was 84.4 in the able category. Overall, the student’s speech ability through modeling techniques increased by 17.6 from 66.8 at the first meeting to 84.4 at the second meeting. From the results of this class action research it can be concluded that the application of modeling techniques can improve the speech skills of Grade VI Catholic Nita 1 Elementary School students